KAPABILITAS BIROKRASI DALAM PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB) DI KECAMATAN MERAL KABUPATEN KARIMUN TAHUN 2013-2016 - Muhamad Hafies; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study was motivated by the issue of bureaucracy in the Building Construction Permit (IMB) service at the Meral District office in Karimun Regency. Attempting to find out how the bureaucracy capabilities in the service of building permits (IMB) through the concept of Bureaucratic Capability in the service of building permits (IMB). As well as knowing what factors faced by the bureaucracy in the service of building permits (IMB) in Meral sub-district. This type of research is qualitative. This study aims to describe systematic and accurate real conditions in the field related to facts and research analysis units, as well as field observations based on certain facts (information). Data collection methods are carried out by means of interviews and documentation. The results of the study explain that the capability of the bureaucracy in the District of Meral is still not good. This is due to the many shortcomings that are seen from Institutional, Human Resources, Finance, and Technical Resources indicators. The deficiencies are significant, especially in technical resources where there is no Standard Operating Procedure (SOP), resulting in an ineffective service process that results in not achieving good bureaucratic capability in the Meral District of Karimun Regency.Key Words: Kapabilitas,Birokrasi Kecamatan, Izin Mendirikan Bangunan (IMB)